Growing Tri Hita Karana-Based Entrepreneurial Mentality in Digital Business for PGSD Students to Face the Era of Society 5.0 - Nyoman Ayu Putri Lestari; I Wayan Lasmawan; I Nengah Suastika (The Es Economics and Entrepreneurship, 2022)
The purpose of this research is to foster a tri hita karana-based entrepreneurial mentality in digital business for PGSD students to face competition in the era of society 5.0. This article links entrepreneurs based on Tri Hita Karana which are included in the principles of Hinduism, digital business and the era of society 5.0 for PGSD students. The application of tri hita karana is closely related to strengthening student character. Because later students as the younger generation must be able to work independently not only relying on muscles but also with the brain. The implementation of Hindu principles, namely Tri Hita Karana, is very closely related to the concept of the Tri Center of Education. This research is included in the type of qualitative data and a documentation study was conducted to collect data. Then for the analysis used is descriptive qualitative analysis. The conclusion of this research is to foster a tri hita karana-based entrepreneurial mentality in digital business for PGSD students to face competition in the era of society 5.0 by releasing and empowering all of students' potentials.